METAPHOR IN THE LANGUAGE OF RELIGION - Pandaripande, Rajeshwari (1990)
The language of religion has been studied from different perspectives by theologians. philosophers, literary critics and linguists. Scholars from these diverse disciplines have focussed on different issues related to the language of religion. Philosophers' primary interest lies in the questions related to the contents while linguists are primarily interested in analyzing the 101m of the language of religion. Thus philosophers such as Ayer, Carnap and Wittgenstein discuss questions such as (a) what kind of reality does language of religion depict, and (b) is language capable of expressing religious contents? and (c) how does language express religion (symbolically, or analogically?), etc. On the other hand linguists such as Ferguson," Rabin s and Samarin" are primarily interested in identifying formal features (phonetic, phonological, syntactic. etc.) which define the 'register' of the language of religion.
Keywords: Linguistic Structure; Metaphor; Metaphor as Ritualistic Symbol; Metaphor: A Point of Inquiry; Metaphor: Definition; Myth; Question of; Sentence; and 'Transcendent Reality